A educação inclusiva: um estudo sobre os sentidos constituídos por alunos em relação à diferença - Moreiras, Viviane Lemos de Jesus (2009)
This research is about inclusion, and it is aimed to contribute to the efforts toward building an inclusive education in Brazil. To study the how differences are perceived by a child, we interviewed 14 elementary school children. In addition, we have more deeply analyzed the interviews of two selected individuals. These two children were chosen due to their structured speech, that included arguments to justify their answers. This study is based on the differences, because we believe it is from them that we give the meaning, collectively, to the diversity that is presented to each individual. The differences are the basis of discrimination, stigma and prejudice and thus the acceptance or not of the proposed inclusive education. We defend an educational proposal that promote the development of values and perceptions for the subjects that are part of it. This is a qualitative research, the theoretical-methodological referential was the socio-historical psychology. The informational analysis was made based on the (meaning cores), and the central categorization was done based on the subjective sense.The information was obtained through the creation and use of flashcards: a game composed of 40 cards in plastic showing pictures of many kinds of children with differences of race, gender, social condition and disability. This study showed us that the differences, represented in flashcards and presented to children, are socially marked and used as an evaluation criteria for the others and ourselves. Therefore, to find the differences of perception, we should not look only at the individual, but realize that the judgments and choices of individuals are referred by a social context. Each child includes in their construction of perceptions, content collectively validated (the perception) and use them to strengthen and maintain these assessments. Senses and meanings are imbricate in a relationship of mutual production. Meet the senses allows us to analyze the perceptions, and learn the perceptions should lead us to the education proposals that are able to interfere in the production of the senses. We believe that inclusive education should prioritize work with the students, should focus on the development of perceptions in relation to the difference than become a source of inequality